"It’s the politics, stupid!": the politicization of anti-corruption in Italy - Sberna, Salvatore (Crime, law and social change, 2013)
This article aims to analyze the relationship between judicial activism against political corruption and electoral accountability. The judiciary plays a pivotal role in enforcing anti-corruption legislation, and, in many countries, courts have moved closer and closer towards that kind of working. In the article, we analyze the conditions under which a judicial prosecution of corrupt practices can also lead to electoral punishment of political misconducts by voters, or to a failure of accountability mechanisms. The latter outcome is more likely to occur if judicial activism is politicized. The ‘politicization’ of anti-corruption initiatives is here defined as an increase in the polarization of opinions, interests, or values about judicial investigations and the extent to which this polarization is strategically advanced towards the political debate by parties, political leaders, and media. By crystallizing a new dimension of political conflict, political actors can negatively affect electoral accountability, diminishing the risk of electoral punishment. We study this phenomenon by analyzing the case of Italy, a country which has experienced high levels of politicization of anti-corruption. However, whether and to what extent anti-corruption policies can be politicized is a question open for many other countries that can take a similar path.